Mercury (not always rising) and the social economy of nineteenth-century Peru - Deustua, José R. (2010)
This study focuses on the Peruvian mining industry of mercury or azogue in the nineteenth century.Mercury was a crucial component for Andean and Mexican silver mining during colonialtimes and still in the first century of Republican Peru. However, it was not the booming industrythat occurred at the end of the sixteenth century, in the second half of the seventeenth, and at thesecond half of the eighteenth century with production peaks at 13 000, 8000 and 7000 quintalsper year. During the nineteenth century it was rather a relative modest industry («not always rising») but also had moments of peak and decline. The article discusses production figures from the1950 by engineers Fernandez Concha, Yates, and Kent, with new statistics coming from archivalsources, which shows important regional levels of production and articulation with silver miningcenters such as Cerro de Pasco. The article also shows that mercury production was not limitedto the old colonial Huancavelica mine of Santa Bárbara but to other areas in the Huancavelicaregion, such as Angaraes and Lircay, or beyond Hunacavelica, such as Chonta in Cerro de Pascoor even Chachapoyas. It also focuses on the conflictive dynamics that mining production meantfor criollo business people, the government, merchants, and indigenous workers. There wereseveral business efforts to revitalize the mine of Santa Bárbara as well as to invest in Huancavelicamercury mining in combination with government initiatives and actions, but it is also clear theaction of mercury merchants, rescatires, who many times rather dealt with workers and humachis,independent laborers or small entrepreneurs, many times Andean Quechua peasants, who ratherbenefitted during the down cycles in mercury production. Finally, after analyzing this particularindustry, the author reflects on the meaning of economic development and historical studies tocriticize U.S. economic historians such as Stephen Haber (from Stanford University) and JohnCoatsworth (from Columbia University) and their view that Latin American countries have to«catch-up» with the capitalist development in the United States and Western Europe, as well aspost-modern and cultural studies which deny the materiality of human life.